Quality of Personal and Professional Life (Journal of Universal Excellence, 2026)
Research Question (RV): What are the positive and negative aspects of a poor work-life balance? What strategies are so important to achieving a good work-life balance?Purpose: The purpose of this research is to explore and highlight the key positive and negative aspects of work-life balance and to identify strategies that can contribute to its improvement. It focuses on understanding how a poorer balance can affect an individual’s quality of life and the effectiveness of organizations, and discusses how different approaches can be used to optimize this balance.Method: For the research, we used a qualitative method, where we reviewed and analyzed domestic and foreign literature on the topic of overtime work and quality of life.Results: he results of the study show that a poorer work-life balance leads to increased stress, reduced mental and physical health, and poorer interpersonal relationships. On the other hand, a good balance contributes to higher productivity, job satisfaction and better personal well-being. Strategies such as flexible working hours, support for mental health and the development of an organizational culture that promotes a balanced life are key to improving balance.Organization: Organizations that promote a good work-life balance experience lower employee turnover, less sick leave, and a more motivated workforce. It recommends that companies should create a more flexible working environment and offer programmes to promote employee well-being.Society: The study highlights that work-life balance is important not only for individuals but also for society as a whole. It emphasises that improved balance can contribute to higher social productivity and the overall health of the population.Originality: This research provides a fresh perspective on the topic of work-life balance by combining perspectives from different disciplines and taking into account recent trends such as teleworking and the digitalisation of the workplace.Constraints/further research: Limitations of the research include its focus on literature and lack of empirical data. Further research could include empirical studies to verify findings and extend the research to different industries and cultural contexts. It would also be useful to explore the long-term effects of different work-life balance strategies.
Keywords: quality of life; stress; productivity; balance; strategies; optimization